Pengaruh Penilaian Kerja, Reward dan Punishment Terhadap Kinerja Karyawan (Studi pada Karyawan Bank BTN Kantor Cabang Medan) - Patarida Sibuea, Grace Renita; Harahap, Kartini; Siregar, Onan Marakali (Jurnal Serambi Ekonomi dan Bisnis, 2024)
The success of a company is determined by employee performance so that the company takes various ways to improve the performance of its employees. Good employee performance will accelerate the achievement of a company's goals, conversely organizational goals cannot be achieved if its employees do not have good performance. Performance appraisal is basically one of the key factors in developing employee performance in a company, it is also necessary to provide rewards and punishments to improve employee performance. The form of this research is quantitative with a sample size of 55 respondents conducted through simple random sampling techniques. Primary data in this study were obtained by distributing questionnaires directly and secondary data were obtained through literature studies. The results of this study indicate that work assessment (X1), reward (X2), punishment (X3) have a significant effect both partially and simultaneously on the performance of employees of Bank BTN Medan Branch Office. The determination coefficient test shows that there is a close relationship between work assessment (X1), reward (X2), punishment (X3) employee performance with an R value of 0.829. Through the adjusted R square value, it is also known that the work assessment variables (X1), reward (X2), and punishment (X3) contribute 66.9% to the employee performance variable, while the remaining 33.1% is influenced by other variables outside this research model.